Structured Heterogeneity in a Marine Terrace Chronosequence: Upland Mottling. Issue 2 (19th February 2016) - Schulz, Marjorie; Stonestrom, Dave; Lawrence, Corey; Bullen, Tom; Fitzpatrick, John; Kyker-Snowman, Emily; Manning, Jane; Mnich, Meagan
Abstract : Core Ideas: The rhizosphere on stable landforms orchestrates elemental redistribution at depth. Rhizospheric processes have long‐term impacts on soil structure and nutrient supply. Soil profile development and mottling are rhizospheric at the studied sites. Rhizogenic mottling under stable uplands may be common in arid to semi‐humid climates. Soil mottles generally are interpreted as a product of reducing conditions during periods of water saturation. The upland soils of the Santa Cruz, CA, marine terrace chronosequence display an evolving sequence of reticulate mottling from the youngest soil (65 ka) without mottles to the oldest soil (225 ka) with well‐developed mottles. The mottles consist of an interconnected network of clay and C‐enriched regions (gray, 2.5Y 6/1) bordered by leached parent material (white, 2.5Y 8/1) within a diminishing matrix of oxidized parent material (orange, 7.5YR 5/8). The mottles develop in soils that formed from relatively uniform nearshore sediments and occur below the depth of soil bioturbation. To explore how a presumably wetland feature occurs in an unsaturated upland soil, physical and chemical characteristics of mottle separates (orange, gray, and white) were compared through the deep time represented by the soil chronosequence. Mineralogical, isotopic, and surface‐area differences among mottle separates indicate that rhizogenic centimeter‐scale mass transfer acting across millennia is an integral part of weathering, pedogenesis, and C and nutrient transfer. Elemental analysis, electron microscopy, and Fe‐isotope systematics indicate that mottle development is driven by deep roots together with their fungal and microbial symbionts. Taken together, these data suggest that deep soil horizons on old stable landforms can develop reticulate mottling as the long‐term imprint of rhizospheric processes. The processes of rhizogenic mottle formation appear to regulate pedogenesis, nutrients, and C sequestration at depth in unsaturated zones.